Abnormal regulation of soluble and anchored IL-6 receptor in monocytes from patients with essential thrombocythemia - Goette, Nora Paula (2010)
Objective: In a previous study, we found increased plasma soluble receptor for interleukin-6 (sIL-6R) levels in patients with essential thrombocythemia (ET) that could promote megakaryopoiesis through IL-6 binding and further interaction with the signal transducer gp130. Here we have searched for the cell source of sIL-6R within mononuclear cells in these patients and the underlying abnormalities involved in its overproduction. Materials and Methods: Thirty patients with the diagnosis of ET were studied. sIL-6R levels were measured by enzyme-linked immunosorbent assay technique in the supernatants of peripheral monocyte and lymphocyte cultures. Expression of membrane-anchored IL-6R was determined by flow cytometry. In order to study the mechanism of sIL-6R production, tumor necrosis factor−α protease inhibitor was added to specifically block IL-6R shedding. Gene expression of sIL-6R levels were evaluated by reverse transcription polymerase chain reaction. Results: Monocytes were the main source of sIL-6R. Besides, in ET patients, monocyte sIL-6R release was higher than that of controls (p = 0.0014). Lymphocytes enhanced monocyte sIL-6R production by cell-mediated contact in normal controls, but this cooperation could not be seen in patients. Membrane expression of IL-6R was increased after monocyte adhesion in ET. sIL-6R synthesis was upregulated in most patients, while messenger RNA was normal. Conclusions: Our results indicate that ET monocytes are responsible for sIL-6R overproduction within mononuclear cells through synthesis upregulation. In addition, the lack of cooperation of lymphocytes in monocyte sIL-6R production in ET could be due to a monocyte abnormality. The agonistic effect of sIL-6R on IL-6 action could contribute to the exacerbated megakaryocytic growth in ET.